Gremlins 2 [videorecording (DVD)] : the new batch - Galligan, Zack; Cates, Phoebe; Glover, John, 1944-; Dante, Joe, 1948- (Warner Bros., 2002)
A Gremlin is captured by a mad scientist, who not only helps it multiply, but give it the ability to talk.